2019
DOI: 10.3389/fmicb.2019.02562
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a recA-Mediated Non-toxigenic Vibrio cholerae O1 Strain to a Toxigenic Strain Using Chitin-Induced Transformation

Abstract: Toxigenic Vibrio cholerae strains, including strains in serogroups O1 and O139 associated with the clinical disease cholera, are ubiquitous in aquatic reservoirs, including fresh, estuarine, and marine environments. Humans acquire cholera by consuming water and/or food contaminated with the microorganism. The genome of toxigenic V. cholerae harbors a cholera-toxin producing prophage (CT-prophage) encoding genes that promote expression of cholera toxin. The CT-prophage in V. cholerae is flanked by two satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Similar to our study, environmental NOVC strains SCE188, SCE200, SCE201, and SCE223 from India isolated in 1997/1998 lacked tcpA genes while ctxAB genes were present ( 38 ). In a previous in vitro study, the possibility of CTX gene transfer from a toxigenic O1 strain to an environmental NOVC strain was confirmed with uncertainty on whether the entire genome was transferred or whether the phage genome was integrated with the recipient chromosome upon transfer ( 39 ). According to our analysis, the entire CTX phage region is transferred from a toxigenic O1 El Tor strain from Australia to environmental NOVC strains.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to our study, environmental NOVC strains SCE188, SCE200, SCE201, and SCE223 from India isolated in 1997/1998 lacked tcpA genes while ctxAB genes were present ( 38 ). In a previous in vitro study, the possibility of CTX gene transfer from a toxigenic O1 strain to an environmental NOVC strain was confirmed with uncertainty on whether the entire genome was transferred or whether the phage genome was integrated with the recipient chromosome upon transfer ( 39 ). According to our analysis, the entire CTX phage region is transferred from a toxigenic O1 El Tor strain from Australia to environmental NOVC strains.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies showed that genetic basis of the emergence of multidrug resistant (MDR) and extensively drug resistant (ExDR) Vibrios and other enteric pathogenic bacteria is mainly due to horizontal gene transfer (HGT) through different types of highly dynamic mobile genetic elements, such as plasmids, integrating conjugative elements, superintegron, transposable elements, and insertion sequences ( Wozniak and Waldor, 2010 ; Kumar et al, 2017 ; Verma et al, 2019 ) that could potentially propagate from one bacteria to other closely or distantly related bacteria. Natural competency in Vibrios allows them to uptake and chromosomally integrate, exogenous DNA coming from multidrug resistant commensal gut bacteria and other sources which ultimately leads to the emergence of drug resistant Vibrios ( Meibom et al, 2005 ; Bag et al, 2019 ; Sinha-Ray et al, 2019 ). A novel “carry-back” mechanism for inter-phylum exchange of genes is also proposed where carrier DNA sequence may be transferred from Proteobacteria to Actinobacteria via conjugative plasmid or integron and then again taken up by Proteobacteria from Actinobacteria through transformation followed by genomic integration through homologous recombination.…”
Section: Mechanisms Of Antimicrobial Resistance In Vibriosmentioning
confidence: 99%
“…1); the average length of DNA fragment taken up is 50 kbp (44). The conversion of V. cholerae O1 serogroup to O139 is suspected to have been caused by natural transformation, because it can be replicated in the laboratory by growth on chitin (45), and even toxigenic conversion may occur by chitin-induced transformation (46). As we have shown here, the superior ability of El Tor V. cholerae to undergo chitin-dependent natural transformation in comparison to classical V. cholerae (even with HapR restored) would be expected to provide an evolutionary advantage to this biotype.…”
Section: Discussionmentioning
confidence: 99%